Analysis of Economic Potential in Stock Zakat in the Indonesian Financial Sector - Nur, Silva Maulida; Valencia, Eka Lintang; Amaroh, Siti (Journal International Dakwah and Communication, 2023)
The aim of this study is to examine the economic potential of zakat shares within Indonesia's expanding financial sector, as it has the capacity to enhance the well-being of individuals and promote economic growth. This type of zakat is analyzed through analytical and descriptive methods, utilizing secondary data from financial reports and related institutions. Despite low levels of community participation, this research indicates that the potential for zakat shares within Indonesia's financial sector is substantial. Through data analysis, it is evident that zakat shares can contribute to the enhancement of the financial sector by increasing liquidity and investor confidence, as well as promoting more inclusive economic growth and equitable distribution of wealth. Consequently, to provide significant economic benefits for the financial sector as a whole, it is necessary to augment public participation in zakat shares and improve zakat infrastructure.